Theoretical and philosophical aspects of special powers of a political community with regard to counter terrorism security - Rosicki, Remigiusz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
The material scope of the analysis undertaken in the text covers the issues concerned with the relationship between two goods. Between the good constituted by community security on the one hand, and the good vested in the power to apply special measures falling within necessary defence and the state of higher necessity. The problem of the relationship between two goods, e.g. a conflict between two goods, can be observed in the competition between the common good and the good of the individual. A similar relation can be noted in the process of derogation from the obligations upon the contemporary political community as regards protection of life and other individual rights and freedoms. Special cases of the conflict between goods include the admissibility of the use of force, violence or restriction of individual freedom. Undoubtedly, situations in which individuals or groups are subjected to torture or have their life taken serve as the most extreme examples of violence use by the political community. All kinds of surveillance measures used by state institutions should be reckoned among the examples concerned with interference in individuals’ private lives. The main purpose of the analysis contained in the text is to present all manner of argumentation concerned with the possibility of applying special measures within or outside the bounds of necessary defence and the state of higher necessity by the political community. In order to elaborate the objective scope of the analysis, the following research questions have been formulated in the text: (1) To what extent is it possible, within the limits of the law and per analogiam to the individual’s adequate actions, for the political community to apply special measures (necessary defence or the state of higher necessity) with the aim of providing security (and in particular counter terrorism security) for itself?, (2) To what extent is it possible, outside the limits of the law and per analogiam to the individual’s adequate actions, for the political community to apply special measures (necessary defence or the state of higher necessity) with the aim of providing security (and in particular counter terrorism security) for itself? The presented analysis is chiefly an overview of a conceptual character with regard to the presentation of the issues concerned with the relationship between such goods as security and special powers of a political community. For the presentation of the legal aspects of this issue textual, functional and systemic interpretations have been applied. Next to the individual kinds of legal interpretation, in the course of argumentation a theoretical reflection on the law is used. The conceptual approach to the title problem makes use of argumentation per analogiam to appropriate actions by an individual when faced with a direct threat, and specified in the provisions of the Polish criminal law – necessary defence and the state of higher necessity.

Zakres przedmiotowy analizy podjętej w tekście obejmuje problematykę relacji między dwoma dobrami. Z jednej strony między dobrem, którym jest bezpieczeństwo wspólnoty, i z drugiej strony – dobrem wyrażającym się w uprawnieniu do stosowania szczególnych środków wpisujących się w ramy obrony koniecznej i stanu wyższej konieczności. Problem relacji między dwoma dobrami, np. konfliktem między dwoma dobrami, zauważyć można w rywalizacji dobra wspólnego i dobra jednostki. Podobną relację zauważyć można w procesie derogacji zobowiązań współczesnej wspólnoty politycznej w zakresie ochrony życia oraz innych praw i wolności jednostki. Za szczególne przypadki kolizji dóbr należy uznać dopuszczalność użycia siły, przemocy i ograniczenia prywatności jednostki. Do najbardziej skrajnych przykładów użycia siły i przemocy przez wspólnotę polityczną należy zaliczyć pozbawienie jednostek lub grup życia i stosowanie wobec nich tortur. Natomiast do przykładów związanych z ingerencją w sferę życia prywatnego jednostki należy zaliczyć wszelkiego rodzaju środki inwigilacji stosowane przez instytucje państwowe. Głównym celem analizy zawartej w tekście jest przedstawienie różnego typu argumentów dotyczących możliwości stosowania szczególnych środków w granicach lub poza granicami obrony koniecznej i stanu wyższej konieczności przez wspólnotę polityczną. W celu uszczegółowienia zakresu przedmiotowego analizy w tekście wskazano następujące pytania badawcze: (1) W jakim zakresie możliwe jest w granicach prawa, per analogiam do adekwatnych działań jednostki, stosowanie szczególnych środków (obrony koniecznej lub stanu wyższej konieczności) przez wspólnotę polityczną w celu zapewnienia jej bezpieczeństwa (w szczególności bezpieczeństwa antyterrorystycznego)?; (2) W jakim zakresie możliwe jest w poza granicami prawa, per analogiam do adekwatnych działań jednostki, stosowanie szczególnych środków (obrony koniecznej lub stanu wyższej konieczności) przez wspólnotę polityczną w celu zapewnienia jej bezpieczeństwa (w szczególności bezpieczeństwa antyterrorystycznego)? Analiza zawarta w tekście ma głównie charakter poglądowy i koncepcyjny w zakresie prezentacji problematyki relacji dóbr, jakimi są bezpieczeństwo i szczególne uprawnienia wspólnoty politycznej. Do prezentacji prawnych aspektów tego zagadnienia wykorzystano interpretację tekstualną, funkcjonalną i systemową. Obok poszczególnych rodzajów interpretacji prawnych w toku argumentacji wykorzystano teoretyczną refleksję nad prawem. W ujęciu koncepcyjnym tytułowego problemu wykorzystano argumentację per analogiam do adekwatnych działań jednostki w chwili bezpośrednio grożącego jej niebezpieczeństwa a określonych w przepisach polskiego prawa karnego – czyli obrony koniecznej i stanu wyższej konieczności.
Teoretyczne i filozoficzne aspekty szczególnych uprawnień wspólnoty politycznej w zakresie bezpieczeństwa antyterrorystycznego
Keywords: security; counter terrorism security; terrorism; common good; necessary defence; state of higher necessity; bezpieczeństwo; bezpieczeństwo antyterrorystyczne; terroryzm; dobro wspólne; obrona konieczna; stan wyższej konieczności